Wildthorn - Eagland, Jane. (Boston : Graphia, 2009)
Seventeen-year-old Louisa Cosgrove is locked away in the Wildthorn Hall mental institution, where she is stripped of her identity and left to wonder who has tried to destroy her life.
Publisher's Weekly
School Library Journal
Wilson's Junior High School
Booklist, September 2010
Bulletin (Center for Children's books), October 2010
Horn Book, May 2011
Keywords: Psychiatric hospitals -- Juvenile fiction; Sex role -- Juvenile fiction; Teenage girls -- Juvenile fiction; Psychiatric hospitals -- Fiction; Sex role -- Fiction; Teenage girls -- Fiction; Gender role -- Fiction; Girls -- Fiction; Psychiatric hospitals -- Fiction; Teenagers -- Fiction